RecombiCraft library construction: A novel method for DNA library cloning and expansion using non-enzymatic single-step DNA recombination and liquid culture. - Yuki Kawai-Harada; Mehrsa Mardikoraem; Katherine Lauro; Vasudha Nimmagadda; Quynh Tong; Kayla Bello; Daniel Woldring; Masako Harada (PLoS ONE)
In this study, we introduce RecombiCraft, an innovative, rapid, and cost-efficient method for constructing DNA libraries in E. coli. This method uses seamless ligation cloning extract (SLiCE) coupled with liquid culture amplification to effectively minimize sequence biases. The technique capitalizes on the natural homologous recombination capabilities of E. coli cell lysates, eliminating the need for multiple purified enzymes and reducing costs. We first synthesized the library backbone and inserts via PCR, employing high-fidelity polymerase to minimize sequence bias. The SLiCE technique was then used to assemble the DNA fragments introduced into E. coli through electroporation. To ensure the integrity of the library, we optimized culture times based on next-generation sequencing analysis which confirmed the minimal sequence bias. The RecombiCraft method demonstrates that this approach is economical and maintains the library's uniformity. By using liquid culture, this method can complete DNA library generation in about 12 hours and final extraction is simple, making it a promising tool for genetic research and biotechnology applications.